International Humanitarian Law Perspective on the Armistice between Russia and Syria - Yordan Gunawan; Marselina Putri Damayanti; Diva Aisya Safitri; Andi Agus Salim (Lex Librum : Jurnal Ilmu Hukum, 2021)
This paper aims to analyze how the perspective of International Humanitarian Law and The 1949 Geneva Conventions are related to the armistice case between Russia and Syria involving civilians as victims of war crimes. By analyzing the applicable international law as the legal basis for the armed conflict case, it is possible to produce an explanation regarding the legal protection provided to civilians as victims of the armistice carried out by Russia in Syria. The type of writing used in this paper is a normative legal study that contains comments, summaries, and thought from several sources written based on the data collected and explained in a statement, not in the form of numbers. The research method used in writing this paper is a normative legal research method that refers to several laws and regulations as guidelines in solving a problem. In the case of the armed conflict in Syria, which has not yet been resolved, even though it has been resolved through an armistice which in fact still result in conflict, the United Nations, as one of the supporters of the world security forum, seeks to resolve it through diplomatic negotiations in order to realize the agreement in the 1949 Geneva Convention as a point of departure clearly related to the resolution of the armed conflict in Syria.